Serum electrolytes and lipid profiles in non-insulin dependent diabetes mellitus patients - Talabani, Namama (Asian Journal of Medical Sciences, 2014)
Background: Diabetes mellitus and hyperlipidemia are the most common metabolic disorder affecting the people all over the world. Hyperglycemia is considered a primary cause of diabetic vascular complications and is associated with impaired electrolytes in some of the metabolic dysfunctions is not clear. Aim: The purpose of this study was conducted to investigate the relationship among diabetes mellitus, lipid profiles and electrolytes (Na+, K+ and Cl-). Methods: In the sera of 85 non insulin-dependent diabetes mellitus NIDDM, 45 with hyperlipidemia, 40 without hyperlipidemia, 50 samples of hyperlipidemia without NIDDM, and 50 non diabetic healthy control subjects. The mean age of the diabetic patients was similar to that of control. The mean duration of the disease was (10.2±5.9) years (2-23) years. From the results, it was discovered that there was a significant decrease in Na+ and Cl- in patients with NIDDM without high level of lipid profile (group I), but our results show that the concentration of K+ not changed significantly. The plasma levels of Na+ and Cl- ions were show significant change in patient with hyperlipidemia without NIDDM (group II), while plasma K+ not changed significantly in this group as compared with control. The mean value of Na+ and Cl- show high significant change in NIDDM patients with high level of lipids profile (group III),were plasma K+ not changed significantly as compared with control group. Conclusion: These finding may explain the role of impaired electrolytes status in NIDDM and hyperlipidemia subjects. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11088 Asian Journal of Medical Sciences Vol.6(3) 2015 38-41